PENGARUH PERSEPSI KORUPSI DAN KUALITAS PELAYANAN FISKUS TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI DI KANTOR PELAYANAN PAJAK PRATAMA CILEGON - Rika Kartika,; Ulfi Jefri,; Fuzi Suhartati, (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2020)
Taxes are used to build infrastructure and public facilities to support the progress of a country, because its role is very central and important in the country, citizens as citizens should understand the importance of taxes and understand how to carry out their rights and obligations related to taxes. This study aims to determine the impact of the perception of corruption and the quality of service tax authorities either jointly or partially on the compliance of individual taxpayers in the Tax Office Primary Cilegon. This study categorized the type of quantitative descriptive with 100 respondents private persons registered in the Tax Office Primary Cilegon as samples and used incidental sampling method. The results showed that the perception of corruption significantly influence adherence individual taxpayer (H1), Quality of Service tax authorities significant effect on compliance with an individual taxpayer (H2), the perception of corruption and the quality of service tax authorities jointly significant effect on tax compliance people private (H3)